Pharmaceutical Advantages of GenoTX-407, A Combination of Extracts from Scutellaria baicalensis Root and Magnolia officinalis Bark - Eun-Jung Yoon; Mi Young Lee; Byoung Il Choi; Kyong Jin Lim; Seung Young Hong; Dongsun Park (Antioxidants, 2020)
Background: Extracts of Scutellaria baicalensis root (SBR) and Magnolia officinalis barks (MOB) possess significant antioxidant, anti-inflammatory, and antimicrobial properties; however, these also exert adverse effects such as cytotoxicity. To overcome the adverse effects, we formulated a combination of the extracts, named GenoTX-407, with SBR and MOB extracts mixed in 5:1 ratio. The antioxidant, antimicrobial, and anti-inflammatory activities of SBR and MOB extracts and GenoTX-407 were evaluated. Methods: To optimize the extraction conditions of SBR and MOB, different ethanol concentrations and extraction times and treatments of the extracts with different solvents for varying time periods were tested. Anti-inflammatory activity was assessed via NO scavenging assay and analysis of anti-inflammatory activity-related gene expression in RAW 264.7 cells. Agar disk diffusion and microdilution assays were used to determine the antimicrobial activity. Antioxidant activity was evaluated through DPPH assay and analyses of peroxidation and antioxidant-related protein expression in HeLa cells. Results: Extraction with 0% ethanol for 2 h and 1.5% phosphoric acid for 0.5 h yielded maximum SBR extracts. For MOB, 50% ethanol extraction for 2 h followed by further extraction in hexane for 0.5 h yielded the highest extracts. SBR (46.1 ± 0.9 %) and MOB (48.9 ± 1.0 %) extracts effectively inhibited NO production, and dose-dependently reduced the expression of TNF-α, iNOS, NF-κB, COX2, and IL-6. MOB and GenoTX-407 inhibited the growth of Escherichia coli, Staphylococcus aureus, Candida albicans, and Propionibacterium acnes, as evidenced in disk diffusion and microdilution assays. SBR (EC50, 107.7 µg/mL and 38.3 µg/mL), MOB (62.41 µg/mL and 72.45 µg/mL), and GenoTX-407 (7.7 µg/mL and 26.4 µg/mL) exhibited excellent antioxidant potency and could scavenge free radicals of DPPH and lipid peroxidation; additionally, SOD, CAT, HO-1, and Nrf2 expression was increased in HeLa cells. SBR showed more potent antioxidant activity than MOB. Contrastingly, MOB exhibited more potent anti-inflammatory and antimicrobial activities than SBR. Interestingly, GenoTX-407 was the most efficient in all the assays, compared with SBR and MOB. Conclusion: This study demonstrated that GenoTX-407, the combination of SBR and MOB, is a potential drug candidate exerting antioxidant and anti-inflammatory effects via the Nrf2/HO-1 and NF-κB signaling pathways.